Institutionalization of Support Networks in the Inter-Family and Friendly Exchanges - Илья Ефимович Штейнберг (Journal of Economic Sociology, 2010)
The study aims to analyze institutionalization of networks of social support in inter-family and friendly exchanges. Social support networks imply a set of various systems of continuously reproduced personified relations and interdependencies of network character based on the traditional institution such as family and friendly mutual aid. This institution is regulated by a complex set of formal rules (laws) as well as informal norms (customs, traditions, and in special cases so-called criminal slang). The paper shows effective methods for research in social support networks in inter-family exchanges. A process of institutionalization is illustrated by the model of unbalanced exchanges among the network members in urban and rural families. The author indicates three basic forms of exchanges of psychological resources in networks of social support. At the core of institutionalization of support networks there are relations that participants of these networks meaningfully construct and some unintended outcomes they have in the end.